Burden of non-hip, non-vertebral fractures on quality of life in postmenopausal women: the Global Longitudinal study of Osteoporosis in Women (GLOW). - Roux, C; Wyman, A; Hooven, F; Gehlbach, S; Adachi, J; Chapurlat, R; Compston, J; Cooper, C; Díez-Pérez, A; Greenspan, S; Lacroix, A; Netelenbos, J; et al. (2012)
UNLABELLED: Among 50,461 postmenopausal women, 1,822 fractures occurred (57% minor non-hip, non-vertebral [NHNV], 26% major NHNV, 10% spine, 7% hip) over 1 year. Spine fractures had the greatest detrimental effect on EQ-5D, followed by major NHNV and hip fractures. Decreases in physical function and health status were greatest for spine or hip fractures. INTRODUCTION: There is growing evidence that NHNV fractures result in substantial morbidity and healthcare costs. The aim of this prospective study was to assess the effect of these NHNV fractures on quality of life. METHODS: We analyzed the 1-year incidences of hip, spine, major NHNV (pelvis/leg, shoulder/arm) and minor NHNV (wrist/hand, ankle/foot, rib/clavicle) fractures among women from the Global Longitudinal study of Osteoporosis in Women (GLOW). Health-related quality of life (HRQL) was analyzed using the EuroQol EQ-5D tool and the SF-36 health survey. RESULTS: Among 50,461 women analyzed, there were 1,822 fractures (57% minor NHNV, 26% major NHNV, 10% spine, 7% hip) over 1 year. Spine fractures had the greatest detrimental effect on EQ-5D summary scores, followed by major NHNV and hip fractures. The number of women with mobility problems increased most for those with major NHNV and spine fractures (both +8%); spine fractures were associated with the largest increases in problems with self care (+11%), activities (+14%), and pain/discomfort (+12%). Decreases in physical function and health status were greatest for those with spine or hip fractures. Multivariable modeling found that EQ-5D reduction was greatest for spine fractures, followed by hip and major/minor NHNV. Statistically significant reductions in SF-36 physical function were found for spine fractures, and were borderline significant for major NHNV fractures. CONCLUSION: This prospective study shows that NHNV fractures have a detrimental effect on HRQL. Efforts to optimize the care of osteoporosis patients should include the prevention of NHNV fractures.